Ketepatan Waktu Penyampaian Laporan Keuangan Ditinjau dari Opini Auditor dan Struktur Kepemilikan - Khotrunida, Alisa; Suhadi, Suhadi; Hardiningsih, Pancawati; Natalina, Sri Anugrah (AKTSAR: Jurnal Akuntansi Syariah, 2023)
The aim of this research is to examine the influence of auditor opinion, managerial ownership, and Institutional Ownership on the timeliness of submitting financial reports. This research uses a quantitative approach supported by secondary data. The population of this research is all manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2019-2021 period. A sample of 57 manufacturing companies registered with ISSI were selected using a purposive sampling method. Based on panel data regression analysis, the results of this study show that the auditor's opinion has a significant effect on the timeliness of submitting financial reports. Managerial ownership and institutional ownership have no effect on the timeliness of submitting financial reports.